HIV PMTCT (PREVENTION OF MOTHER-TO-CHILD TRANSMISSION) PROGRAM IMPLEMENTATION: A LITERATURE REVIEW - Fadila, Nadia Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
ABSTRACTHIV PMTCT (Prevention of Mother-to-Child Transmission) Program implementation: A Literature Review. Humans infected with HIV (Human Immunodeficiency Virus) are a common health issue among reproductive-age people. White blood cells are infected by the HIV virus, which lowers human immunity. AIDS (Acquired Immune Deficiency Syndrome) is the accumulation of symptoms that result from a weakened immune system brought on by HIV infection. One of the most important factors in disease transmission is vertical dissemination or transmission from mother to child. The World Health Organization launched the prevention of mother-to-child transmission (PMTCT) initiative as one of the worldwide strategies. This study's objective is to assess how well the PMTCT program prevents HIV/AIDS from being passed from mother to child. The literature review employs PRISMA methodology, identifies 15 relevant English articles published in the last five years (2018-2023) via Pubmed, Science Direct, Scopus, BMC Journal, and Oxford Academic, and generates this information using English. Consequently, the effectiveness of measures in preventing HIV from being transmitted from mother to child with PMTCT is very high if they are appropriately administered. Multiple stakeholders are required to influence the effectiveness of PMTCT services based on various factors.Keywords: HIV/AIDS, PMTCT, Preventive MeasuresABSTRAK Implementasi Program PMTCT (Prevention of Mother-to-Child Transmision) pada Penyakit HIV: Sebuah Tinjauan Literatur.Infeksi HIV (Human Immunodeficiency Virus) merupakan masalah kesehatan yang umum terjadi terutama pada masyarakat usia subur. Sel darah putih yang terinfeksi virus HIV menyebabkan terjadinya penurunan kekebalan tubuh manusia. AIDS (Acquired Immune Deficiency Syndrome) merupakan akumulasi gejala akibat melemahnya sistem kekebalan tubuh akibat infeksi HIV. Salah satu faktor ter penting dalam penularan penyakit adalah penyebaran atau penularan vertical dari ibu kea nak. Organisasi Kesehatan Dunia (WHO) meluncurkan inisiatif pencegahan dan penularan dari ibu kea nak (PMTCT) sebagai salah satu strategi pencegahan di seluruh dunia. Tujuan penelitian ini adalah untuk menilai seberapa baik program PMTCT dalam mencegah penularan HIV/AIDS dari ibu ke anak. Tinjauan literatur menggunakan metode PRISMA dengan mengidentifikasi 15 artikel berbahasa ingggris yang relevan dan diterbitkan dalam lima tahun terakhir (2018-2023) melalui Pubmed, Science Direct, Scopus, BMC Journal, dan Oxford Academic serta menghasilkan informasi berbahasa Inggris. Melalui tinjauan literatur ini dapat disimpulkan bahwa efektivitas tindakan pencegahan penularan HIV dari ibu ke anak sangat tinggi apabila dilakukan dengan tepat. Dibutuhkan banyak pemangku kepentingan untuk mempengaruhi efektivitas layanan PMTCT berdasarkan berbagai faktor. Kata kunci: HIV/AIDS, PMTCT. Tindakan Pencegahan